Inventering av plantskog med laserscanning och digitalt flygfoto - Korpela, Ilkka; Tuomola, Tuukka; Tokola, Timo; Dahlin, Bo (Metsäntutkimuslaitos, 2009)
Referat av artikeln: Korpela, I., Tuomola, T., Tokola, T. & Dahlin, B. 2008. Appraisal of seedling stand vegetation with airborne imagery and discrete-return LiDAR – an exploratory analysis. Silva Fennica 42(5): 753–772.
Tutkimusseloste